2006
DOI: 10.1111/j.1365-2044.2006.04652.x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the site of tracheal tube impingement during nasotracheal fibreoptic intubation*

Abstract: Summary This study examines the incidence and site of tracheal tube impingement during nasotracheal fibreoptic intubation, and the efficacy of anticlockwise tube rotation to overcome the problem. Forty‐three patients underwent fibreoptic‐assisted nasotracheal intubation using a preformed nasal tube, and a second fibrescope was used to observe any obstruction to passage of the tracheal tube. Impingement occurred in 10 cases, with the most common site being the right arytenoid cartilage. Rotation resulted in suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
63
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 29 publications
(45 reference statements)
3
63
0
2
Order By: Relevance
“…We suggest that tracheal extubation be included in the initial test of competency and be given the same importance as intubation. Although not its intent, we found that Kidner and Laurence's study on basic airway management by junior doctors highlighted how Advanced Life Support (ALS) teaching of basic airway management can differ from our anaesthetic practice [1]. Whilst the authors seem to suggest that ALS may be beneficial, we believe this study exposes the limitations of ALS as much as it demonstrates its strength.…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…We suggest that tracheal extubation be included in the initial test of competency and be given the same importance as intubation. Although not its intent, we found that Kidner and Laurence's study on basic airway management by junior doctors highlighted how Advanced Life Support (ALS) teaching of basic airway management can differ from our anaesthetic practice [1]. Whilst the authors seem to suggest that ALS may be beneficial, we believe this study exposes the limitations of ALS as much as it demonstrates its strength.…”
mentioning
confidence: 78%
“…We read with interest the recent article on the determination of site of tracheal tube impingement during nasotracheal fibreoptic intubation [1]. The conclusion of the study was that the most common site of impingement is the right arytenoid cartilage, as shown for orotracheal fibreoptic intubation [2].…”
Section: Railroading Tracheal Tubes Over a Fibrescopementioning
confidence: 99%
See 1 more Smart Citation
“…This method has been associated with complications and challenges related to the design of the standard ETT, particularly tissue trauma and inability to redirect and pass by anatomic structures. 51,52 To help address this, the Parker Flex-Tip tube (Parker Medical, Englewood, Colorado) has a soft, flexible, hemispherical, curved tip pointing toward the center of the distal lumen of the tube, rather than the straight, stiff, right-sided tip of the standard ETT (Fig. 6).…”
Section: Other Modificationsmentioning
confidence: 99%
“…Other techniques include rotating the ETT counterclockwise before applying pressure to facilitate its advancement. 3 However, proximal rotation does not always result in an equal degree of rotation at the distal tip, 4 and the tip of the tracheal tube may repeatedly abut the laryngeal wall despite these above measures, and fail to pass into the trachea.…”
Section: Another Use Of Magill Forceps To Assist Nasotracheal Intubationmentioning
confidence: 99%